Correction of Progressive Severe Cervical Kyphosis in a 21-Month-Old Patient With NF1: Surgical Technique and Review of Literature. Issue 1 (26th July 2018) - Vigneswaran, Krishanthan; Sribnick, Eric A; Reisner, Andrew; Chern, Joshua
Abstract: BACKGROUND: Severe cervical kyphosis in the setting of neurofibromatosis type 1 (NF1) is a rare manifestation of the disease in the pediatric population. Dystrophic and immature bone complicate the placement of hardware necessary for surgical correction of alignment and a review of the literature yields 4 cases of pediatric patients with NF1 requiring surgical intervention in which the youngest patient was 10 yr old. OBJECTIVE: To report the case of an 11-mo-old female with NF1 who presented with a plexiform cervical neurofibroma and focal cervical kyphosis. A comprehensive review of the literature and a detailed description of nonsurgical and surgical management for this patient population is described. METHODS: A literature review was completed for article reviewing management of pediatric patients with cervical spine injuries and NF1. The patient's chart was reviewed and the patient was followed for a year to provide adequate follow-up. Institutional Review Board (IRB)/ethics committee approval and patient consent were neither required nor sought for this study. RESULTS: The literature was reviewed, summarized, and utilized for operative planning and postoperative management. Postoperative imaging and 1-yr follow-up imaging showed anterior construct and lateral mass fusion, restoration of cervical alignment, and no neurological deficits. CONCLUSION: This is the youngest reported patient to have surgical cervical kyphosis correction in the setting of NF1. A review of the literature helped develop a long-term plan and shape a novel same-day front-back-front approach to restore alignment that will be of use to teams managing these complex patients in the future.